Epistemologias de mulheres negras de terreiros, memórias e saberes: o sagrado chão, cabaça política de conhecimento ancestral - Maciel, Marilene Geronimo da Silva (2025)
The research focuses on epistemological actions in the construction of knowledge as ancestral technology, based on the unique political actions of black women from terreiros in the circumscribed territory of Cidade Ademar, located in the southern region of São Paulo. The intersections (individual, collective, social and political memories) are made invisible in the facets of structural racism, materialized in (historical) religious racism, sexism, gender violence, the commodification of the sacred, socio-spatial, racial, environmental and economic segregation. These power relations have an impact on the real possibility of combating the multiple dimensions of religious racism, which permeates African descendants in diaspora in Brazil, and the terreiro peoples, who come from religions of African origin. In this context, the aim is to find out how the political memory of black women from African-derived terreiros contributes from an epistemological perspective to the political and social formation of the territory. The analysis is based on theoretical studies of bibliographical research, mapping of terreiros, and field research that made it possible to approach the epistemological and political paths of Iyalorixás Sintia de Ósàynín, Cida de Oya and Luciana de Oya. Relating what is part of the very existence and memory of black women of African origin, not just the existential struggles, but the thread of the matriarchal ancestral heritage in the construction of the narratives and politics of the female leaders of terreiro as an identity place of ancestry. The way that terreiro peoples have found to strengthen their own humanities and guarantee their sacred practices, given structural racism. As a central epistemological finding of the research, highlighted in Item 8 of the dissertation, it should be noted that the interviews with the three Iyalorixás themselves are configured as symbolic gourds - wombs of living, complex and politically situated knowledge. The life narratives and speeches of these black terreiro women emerge as an ancestral methodology that puts a strain on academic work and creates new paths for the production of knowledge. By placing listening as a methodology, orality as an archive and ancestry as a foundation, the research recognizes these women as intellectuals of territory, memory and praxis